Metal ion embedded nano vanadium-based compound-graphene modified diaphragm and preparation method thereof
By modifying the nanovanaphthalene compound and graphene embedded in metal ions on the lithium-sulfur battery separator, the performance problems caused by the elemental sulfur insulation and lithium polysulfide shuttle effect of lithium sulfide are solved, and higher electrochemical performance and cycle life are achieved.
Patent Information
- Application Number
- CN202411949452.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Due to the insulation of elemental sulfur, lithium sulfur batteries have low utilization rate and poor rate performance, and lithium polysulfide generated during charging and discharging leads to a shuttle effect, resulting in poor electrochemical reversibility, fast capacity decay and short cycle life.
By uniformly attaching the nanovanaphthalene-modified separator with metal ions to the cell separator, a nanovanaphthalene-modified separator with metal ions is formed. The strong adsorption and catalytic ability of the nanovanaphthalene-based compound and the high conductivity of graphene are used to synergistically inhibit the shuttle effect of polysulfides and accelerate the redox kinetic process.
Effectively inhibit the shuttle effect of polysulfides, accelerate the redox kinetics process, improve the utilization rate of active substances, and significantly improve the electrochemical performance and cycle life of lithium-sulfur batteries.
Smart Images

Figure CN119764757A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a metal ion embedded nano vanadium-based compound-graphene modified diaphragm and a preparation method thereof, belonging to the field of functional materials. Background Art
[0002] Elemental sulfur has the advantages of high theoretical specific capacity (1675mAh / g), low price, abundant reserves, and relatively friendly environment. Therefore, lithium-sulfur batteries have also become a hot topic in the field of high-energy-density batteries. However, there are still many problems in the commercial application of lithium-sulfur batteries: for example, 1) elemental sulfur is an insulator of electrons and ions at room temperature. The insulation of elemental sulfur will lead to low utilization rate of sulfur active substances and poor rate performance; 2) during the charge and discharge process, lithium polysulfide that is easily soluble in the electrolyte is generated inside the battery, forming the so-called "shuttle effect". The "shuttle effect" will lead to irreversible loss of sulfur active substances, poor electrochemical reversibility, and rapid capacity decay, resulting in a short battery cycle life. Therefore, designing and preparing materials that promote charge migration, inhibit the shuttle effect, and accelerate the catalytic conversion of polysulfides is crucial to promoting the practical application of lithium-sulfur batteries.
[0003] The diaphragm in the lithium-sulfur battery can not only effectively provide a lithium ion diffusion path, but also physically separate the positive and negative electrodes to prevent short circuits, and can also regulate the transmission behavior of lithium ions. Using modified battery diaphragms to improve the performance of lithium-sulfur batteries is a relatively good strategy. The modified battery diaphragm can not only hinder the shuttling of polysulfides, but also accelerate the conversion of polysulfides. In addition, to a certain extent, it can also improve the wettability and thermal stability of the diaphragm. In recent years, people have conducted research on the above bottleneck problems in the application of lithium-sulfur batteries and have made certain progress. A lot of work has also been done on the modification of diaphragms to improve the performance of lithium batteries. Therefore, modification research on diaphragm materials can effectively improve the electrochemical properties of lithium-sulfur batteries and provide support for the industrial application of lithium-sulfur batteries.
[0004] Vanadium has multiple oxidation states, and vanadium-based materials have an open crystal structure, which makes vanadium-based materials show excellent electrochemical properties and have broad prospects in energy storage materials and catalytic materials. For example, transition metal nitride vanadium nitride (VN) is a potential electrode material, which has attracted more and more attention due to its metal-like high conductivity, pseudocapacitance, high density and platinum-like catalytic performance. Therefore, the present invention uses vanadium-based compounds to modify the diaphragm, through the strong adsorption and catalytic ability of nano-vanadium-based compounds, and the high conductivity of graphene. The synergistic effect of the two can effectively inhibit the shuttle effect of polysulfides, accelerate the redox kinetics process, and improve the utilization rate of active substances, which is expected to significantly improve the electrochemical performance of lithium-sulfur batteries. Summary of the invention
[0005] The purpose of the present invention is to solve some inherent defects of lithium-sulfur batteries. The present invention provides a metal ion embedded nano-vanadium-based compound-graphene modified diaphragm and a preparation method thereof.
[0006] The technical solution for implementing the present invention is as follows:
[0007] A metal ion embedded nano vanadium-based compound-graphene modified diaphragm is disclosed. The metal ion embedded nano vanadium-based compound and graphene are uniformly attached to the battery diaphragm by a suction filtration method, thereby obtaining the metal ion embedded nano vanadium-based compound-graphene modified diaphragm.
[0008] Specifically, the metal ion embedded nano vanadium-based compound includes one or more of metal ion embedded nano vanadium dioxide, metal ion embedded nano vanadium nitride, metal ion embedded nano vanadium sulfide, metal ion embedded nano vanadium carbide, surface nitrided metal ion embedded nano vanadium oxide, and surface sulfided metal ion embedded nano vanadium oxide.
[0009] A method for preparing a metal ion embedded nano vanadium-based compound-graphene modified diaphragm, wherein nano vanadium-based compound and graphene are uniformly attached to a battery diaphragm by coating, filtration or spraying, thereby obtaining a nano vanadium-based compound-graphene modified diaphragm.
[0010] Further preferably, the nano vanadium-based compound is nano vanadium dioxide embedded with metal ions, and the preparation process is: adding vanadium pentoxide to a metal salt solution, stirring for 72-144 hours, centrifuging and washing to obtain a precursor, then adding the precursor to a water and organic mixed liquid, the volume ratio of water to organic liquid is between 1:2-1:10, placing it in a reactor and heating it at a heating temperature of 140-200°C for 6-36 hours, centrifuging and washing to obtain nano vanadium dioxide embedded with metal ions.
[0011] Further preferably, the nano-vanadium-based compound is a product of further processing of metal ion-embedded nano-vanadium dioxide, and the metal ion-embedded nano-vanadium dioxide is placed in a tubular furnace and heated, under the conditions of adding a nitrogen source, a sulfur source, and a carbon source, the heating temperature is 500-800° C., and the heating time is 0.1-4 hours to obtain metal ion-embedded nano-vanadium nitride, metal ion-embedded nano-vanadium sulfide, metal ion-embedded nano-vanadium carbide, surface nitrided metal ion-embedded nano-vanadium oxide, or surface sulfided metal ion-embedded nano-vanadium oxide.
[0012] Specifically, the nitrogen source includes ammonia, urea, and melamine; the sulfur source includes hydrogen sulfide, thiourea, and sulfur; and the carbon source includes carbon powder, glucose, and sucrose.
[0013] Specifically, the metal salt is one, two, three or more of sodium chloride, lithium chloride, zinc chloride, potassium chloride, calcium chloride, magnesium chloride, cobalt chloride, nickel chloride, iron chloride and copper chloride.
[0014] Specifically, the organic liquid is one, two or more of ethanol, ethylene glycol, polyethylene glycol 200, polyethylene glycol 400, and polyethylene glycol 600.
[0015] The present invention synthesizes a metal ion embedded nano vanadium-based compound-graphene modified diaphragm, which can effectively inhibit the shuttle effect of polysulfide, accelerate the redox kinetic process, improve the utilization rate of active substances, and significantly improve the electrochemical performance of lithium-sulfur batteries through the synergistic effect of the strong adsorption and catalytic ability of the one-dimensional nano vanadium-based compound and the high conductivity of graphene.
[0016] The metal ion embedded one-dimensional nano vanadium-based compound-graphene modified diaphragm involved in the present invention has simple preparation process, safe reaction conditions, simple operation, and reagents involved in the reaction have little harm to the environment, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the X-ray diffraction pattern of the nano-vanadium dioxide embedded with metal zinc ions prepared in Example 1;
[0018] Figure 2 This is a scanning electron microscope image of the nano-vanadium dioxide material embedded with metal zinc ions prepared in Example 1:
[0019] Figure 3 This is a cross-sectional view of the nano-vanadium dioxide-graphene modified diaphragm embedded with metal zinc ions prepared in Example 1;
[0020] Figure 4 Surface distribution diagram of Zn, V, and O elements in the cross section of the nano-vanadium dioxide-graphene modified diaphragm embedded with metal zinc ions prepared in Example 1;
[0021] Figure 5 This is a photo of the nano-vanadium dioxide-graphene modified diaphragm with metal zinc ions embedded therein prepared in Example 1;
[0022] Figure 6 The discharge test results of the battery using the material prepared in Example 1 at different current densities such as 167.5mA / g, 335mA / g, 837.5mA / g, 1675mAh / g, and 3350mA / g;
[0023] Figure 7 The comparison diagram of the cycle life curve of the battery prepared in Example 2 at a current density of 1675 mAh / g;
[0024] Figure 8 The figures are discharge test results of the battery prepared in Example 3 at different current densities such as 1675 mAh / g. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned objects, features and advantages of the present application more obvious and easy to understand, the present application is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0026] The present invention provides a method for preparing a nano-vanadium-based compound-graphene modified diaphragm embedded with metal ions, and then uniformly attaching the nano-vanadium-based compound and graphene to the battery diaphragm by coating, filtration or spraying, thereby obtaining the nano-vanadium-based compound-graphene modified diaphragm.
[0027] The nano vanadium-based compound is a nano vanadium dioxide embedded with metal ions. The preparation process is as follows: adding vanadium pentoxide to a metal salt solution, stirring for 72-144 hours, centrifuging, washing, obtaining a precursor, then adding the precursor to a water and organic mixed solution, the volume ratio of water to the organic liquid is between 1:2-1:10, placing it in a reactor for heating, the heating temperature is 140-200°C, the heating time is 6-36 hours, centrifuging, washing, obtaining a nano vanadium dioxide embedded with metal ions. The metal salt is one, two, three or more of sodium chloride, lithium chloride, zinc chloride, potassium chloride, calcium chloride, magnesium chloride, cobalt chloride, nickel chloride, ferric chloride, and copper chloride. The organic liquid is one, two or more of ethanol, ethylene glycol, polyethylene glycol 200, polyethylene glycol 400, and polyethylene glycol 600.
[0028] The nano-vanadium-based compound is a product of further processing of nano-vanadium dioxide embedded with metal ions. The nano-vanadium dioxide embedded with metal ions is placed in a tube furnace and heated. Under the conditions of adding nitrogen source, sulfur source and carbon source, the heating temperature is 500-800°C and the heating time is 0.1-4 hours to obtain nano-vanadium nitride embedded with metal ions, nano-vanadium sulfide embedded with metal ions, nano-vanadium carbide embedded with metal ions, nano-vanadium oxide embedded with metal ions on the surface nitrided, or nano-vanadium oxide embedded with metal ions on the surface sulfided. The nitrogen source includes ammonia, urea and melamine; the sulfur source includes hydrogen sulfide, thiourea and sulfur; and the carbon source includes carbon powder, glucose and sucrose.
[0029] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0030] Example 1
[0031] Metal zinc ion embedded nano vanadium dioxide-graphene modified diaphragm and preparation method thereof:
[0032] (1) First, vanadium pentoxide is added to a zinc chloride solution, stirred for 96 hours, centrifuged, and washed to obtain a zinc ion embedded vanadium pentoxide precursor.
[0033] (2) adding the prepared zinc ion embedded vanadium pentoxide precursor to a mixture of water and ethylene glycol, wherein the volume ratio of water to ethylene glycol is between 2:1, placing the mixture in a reactor and heating it at 180° C. for 12 hours, centrifuging and washing, and obtaining zinc ion embedded nano-vanadium dioxide. Figure 1 is the X-ray diffraction pattern of zinc ion embedded vanadium dioxide, Figure 2 This is a scanning electron micrograph of vanadium dioxide embedded with zinc ions. Figure 2 As shown, the zinc ion embedded vanadium dioxide appears as nanorods and nanowires with a length distribution of 1 to 3 microns, and the zinc ion embedded vanadium dioxide appears as a shape with a diameter of 10 to 80 nanometers.
[0034] (3) Modification of the diaphragm: Disperse the zinc ion embedded nano-vanadium dioxide and graphene in an ethanol solvent at a mass fraction of 9:1 by ultrasonication and stirring to obtain a dispersion. Then, the zinc ion embedded nano-vanadium dioxide-graphene dispersion is uniformly attached to the battery diaphragm by suction filtration, thereby obtaining a zinc ion embedded nano-vanadium dioxide-graphene modified diaphragm. Figure 3 A cross-sectional view of vanadium dioxide with zinc ions embedded in it. Figure 4 The surface distribution of Zn, V, and O elements on the vanadium dioxide-graphene modified diaphragm embedded with metal zinc ions. Figure 5 This is a photo of a vanadium dioxide-graphene modified separator with metal zinc ions embedded in it. Figure 3 As shown in FIG. 1 , vanadium dioxide and graphene are evenly distributed on the surface of the diaphragm, and the thickness of the modified layer on the cross section of the diaphragm is between 40 and 50 microns. Figure 4 As shown, the Zn, V, and O elements in the modified layer of the diaphragm cross section are evenly distributed.
[0035] (4) A lithium-sulfur battery was assembled in a glove box using the above-prepared zinc ion embedded nano-vanadium dioxide-graphene modified diaphragm, metallic lithium as the negative electrode, and carbon-sulfur as the positive electrode. The electrolyte was anhydrous lithium nitrate with an additive of 0.1 mol / L, the solvent was a mixed solution of 1,3-dioxolane and ethylene glycol dimethyl ether in a volume ratio of 1:1, and a 1.0 mol / L lithium di(trifluoromethylsulfonyl)imide solution. The carbon-sulfur positive electrode was obtained by mixing and grinding carbon bp2000 and elemental sulfur in a ratio of 2:8 and heating at 155°C for 12 hours. At current densities such as 167.5mA / g, 335mA / g, 837.5mA / g, 1675mAh / g, and 3350mA / g, the charge and discharge cycle life test results are as follows Figure 6 As shown. For comparison, the battery using an unmodified separator was assembled according to the above steps. At 167.5 mA / g, the first week discharge capacity of the battery electrode using the PP separator was 1032.6 mAh / g, while the maximum discharge capacity of the battery electrode using the zinc ion embedded nano vanadium dioxide-graphene modified separator was 1468.5 mAh / g. The maximum discharge capacity of the battery using the zinc ion embedded nano vanadium dioxide-graphene modified separator was 1.42 times that of the battery electrode using the PP separator. At 167.5mA / g, the first-week discharge capacity of the battery electrode using the zinc ion embedded nano-vanadium dioxide modified separator is 1313.2mAh / g, while the maximum discharge capacity of the battery electrode using the zinc ion embedded nano-vanadium dioxide-graphene modified separator is 1468.5mAh / g, and the maximum discharge capacity of the battery using the zinc ion embedded nano-vanadium dioxide-graphene modified separator is 1.25 times that of the battery electrode using the zinc ion embedded nano-vanadium dioxide modified separator. At 167.5mA / g, the first-week discharge capacity of the battery electrode using the graphene modified separator is 1169.8mAh / g, while the maximum discharge capacity of the battery electrode using the zinc ion embedded nano-vanadium dioxide-graphene modified separator is 1468.5mAh / g, and the maximum discharge capacity of the battery using the zinc ion embedded nano-vanadium dioxide-graphene modified separator is 1.12 times that of the battery electrode using the graphene modified separator.
[0036] At 3350mA / g, the first-week discharge capacity of the battery electrode using the PP separator was 395.2mAh / g, while the maximum discharge capacity of the battery electrode using the zinc ion embedded nano-vanadium dioxide-graphene modified separator was 868.4mAh / g, and the maximum discharge capacity of the battery using the zinc ion embedded nano-vanadium dioxide-graphene modified separator was 2.2 times that of the battery electrode using the PP separator. At 3350mA / g, the first-week discharge capacity of the battery electrode using the zinc ion embedded nano-vanadium dioxide modified separator was 358.3mAh / g, while the maximum discharge capacity of the battery electrode using the zinc ion embedded nano-vanadium dioxide-graphene modified separator was 868.4mAh / g, and the maximum discharge capacity of the battery using the zinc ion embedded nano-vanadium dioxide-graphene modified separator was 2.42 times that of the battery electrode using the zinc ion embedded vanadium dioxide modified separator. At 3350mA / g, the first-week discharge capacity of the graphene-modified diaphragm battery electrode was 584.7mAh / g, while the maximum discharge capacity of the battery electrode using the zinc ion embedded nano-vanadium dioxide-graphene modified diaphragm was 868.4mAh / g. The maximum discharge capacity of the battery using the zinc ion embedded vanadium dioxide-graphene modified diaphragm is 1.48 times that of the graphene-modified diaphragm battery electrode.
[0037] Example 2
[0038] Metal zinc sodium dual ion embedded vanadium oxide-graphene modified diaphragm and preparation method thereof:
[0039] (1) First, vanadium pentoxide is added to a zinc chloride solution, stirred for 96 hours, centrifuged, and washed to obtain a zinc ion embedded vanadium pentoxide precursor. Then, the zinc ion embedded vanadium pentoxide precursor is added to a zinc chloride solution, stirred for 72 hours, centrifuged, and washed to obtain a zinc and sodium dual ion embedded vanadium pentoxide precursor.
[0040] (2) adding the prepared metallic zinc sodium dual ion embedded vanadium pentoxide precursor to a mixture of water and ethylene glycol, wherein the volume ratio of water to ethylene glycol is between 1:2, placing the mixture in a reaction kettle and heating it at 180° C. for 12 hours, centrifuging and washing, and obtaining metallic zinc sodium dual ion embedded vanadium oxide.
[0041] (3) Modification of the diaphragm: Disperse the vanadium oxide and graphene embedded with metallic zinc and sodium ions at a mass ratio of 9:1 in an ethanol solvent by ultrasonication and stirring to obtain a dispersion. Then, the vanadium oxide-graphene dispersion embedded with metallic zinc and sodium ions is uniformly attached to the battery diaphragm by suction filtration, thereby obtaining a diaphragm modified with vanadium oxide-graphene embedded with metallic zinc and sodium ions.
[0042] (4) A lithium-sulfur battery was assembled in a glove box using the vanadium oxide-graphene modified diaphragm prepared above with metallic zinc-sodium dual ions embedded, metallic lithium as the negative electrode, and carbon-sulfur as the positive electrode. The electrolyte was anhydrous lithium nitrate with an additive of 0.1 mol / L, the solvent was a mixed solution of 1,3-dioxolane and ethylene glycol dimethyl ether in a volume ratio of 1:1, and a 1.0 mol / L lithium di(trifluoromethylsulfonyl)imide solution. The carbon-sulfur positive electrode was obtained by mixing and grinding carbon bp2000 and elemental sulfur in a ratio of 2:8 and heating at 155°C for 12 hours. At a current density of 1675 mAh / g, the charge and discharge cycle life test results are as follows. Figure 7 As shown. For comparison, the battery using an unmodified separator was assembled according to the above steps. At 1675 mA / g, the first-week discharge capacity of the battery electrode using the PP separator was 279.0 mAh / g, while the maximum discharge capacity of the battery electrode using the separator modified by vanadium oxide-graphene with dual zinc and sodium ions was 1088.7 mAh / g, and the maximum discharge capacity of the battery electrode using the separator modified by vanadium oxide-graphene with dual zinc and sodium ions was 3.9 times that of the battery electrode using the PP separator. At 1675 mA / g, after 300 cycles, the first-week discharge capacity of the battery electrode using the PP separator was 461.8 mAh / g, while the maximum discharge capacity of the battery electrode using the separator modified by vanadium oxide-graphene with dual zinc and sodium ions was 581.0 mAh / g, and the maximum discharge capacity of the battery electrode using the separator modified by vanadium oxide-graphene with dual zinc and sodium ions was 1.25 times that of the battery electrode using the PP separator.
[0043] Example 3
[0044] Metal zinc ion embedded vanadium nitride-graphene modified diaphragm and preparation method thereof:
[0045] (1) First, vanadium pentoxide is added to a zinc chloride solution, stirred for 96 hours, centrifuged, washed, and freeze-dried to obtain a zinc ion embedded vanadium pentoxide precursor.
[0046] (2) adding the prepared zinc ion embedded vanadium pentoxide precursor to a mixture of water and ethylene glycol, wherein the volume ratio of water to ethylene glycol is between 2:1, placing the mixture in a reactor and heating it at 180° C. for 12 hours, centrifuging and washing, and obtaining zinc ion embedded nano-vanadium dioxide.
[0047] (3) The prepared zinc ion embedded vanadium dioxide precursor is heated to 600° C. for 1 hour under the condition of adding ammonia gas to obtain metal zinc ion embedded vanadium nitride.
[0048] (4) Modification of the diaphragm: Disperse the zinc ion embedded vanadium nitride and graphene in an ethanol solvent at a mass fraction of 9:1 by ultrasonication and stirring to obtain a dispersion. Then, the metal zinc ion embedded vanadium nitride-graphene dispersion is uniformly attached to the battery diaphragm by suction filtration, thereby obtaining a zinc ion embedded vanadium nitride modified diaphragm.
[0049] (5) A lithium-sulfur battery was assembled in a glove box using the zinc ion embedded vanadium nitride-graphene modified diaphragm prepared above, metallic lithium as the negative electrode, and carbon-sulfur as the positive electrode. The electrolyte was anhydrous lithium nitrate with an additive of 0.1 mol / L, the solvent was a mixed solution of 1,3-dioxolane and ethylene glycol dimethyl ether in a volume ratio of 1:1, and a 1.0 mol / L lithium di(trifluoromethylsulfonyl)imide solution. The carbon-sulfur positive electrode was obtained by mixing and grinding carbon bp2000 and elemental sulfur in a ratio of 2:8 and heating at 155°C for 12 hours. At a current density of 1675 mAh / g, the charge and discharge cycle life test results are as follows. Figure 8 As shown. At 1675mA / g, the maximum discharge capacity of the battery electrode using the vanadium nitride-graphene modified separator embedded with metal zinc ions is 1040.9mAh / g. After 150 cycles, the discharge capacity of the battery electrode is 767.8mAh / g.
[0050] Finally, it should be noted that the described embodiments are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
Claims
1. A metal ion embedded nano-vanadium-based compound-graphene modified diaphragm, characterized in that: The metal ion embedded nano-vanadium-based compound and graphene are uniformly attached to the battery separator by the method of suction filtration, so as to obtain the metal ion embedded nano-vanadium-based compound-graphene modified separator.
2. The metal ion embedded nano vanadium-based compound-graphene modified diaphragm according to claim 1, characterized in that: The metal ion embedded nano vanadium-based compound includes one or more of metal ion embedded nano vanadium dioxide, metal ion embedded nano vanadium nitride, metal ion embedded nano vanadium sulfide, metal ion embedded nano vanadium carbide, surface nitrided metal ion embedded nano vanadium oxide, surface sulfided metal ion embedded nano vanadium oxide.
3. A method for preparing a metal ion embedded nano-vanadium-based compound-graphene modified diaphragm, characterized in that: The nano-vanadium-based compound and graphene are uniformly attached to the battery separator by coating, filtration or spraying, thereby obtaining a nano-vanadium-based compound-graphene modified separator.
4. The method for preparing the metal ion embedded nano-vanadium-based compound-graphene modified diaphragm according to claim 2, characterized in that: The nano vanadium-based compound is nano vanadium dioxide embedded with metal ions, and the preparation process is: adding vanadium pentoxide to a metal salt solution, stirring for 72-144 hours, centrifuging, washing, and obtaining a precursor, then adding the precursor to a water and organic mixed liquid, wherein the volume ratio of water to the organic liquid is between 1:2 and 1:10, placing the precursor in a reactor for heating at a temperature of 140-200°C for 6-36 hours, centrifuging, washing, and obtaining the nano vanadium dioxide embedded with metal ions.
5. The method for preparing the metal ion embedded nano-vanadium-based compound-graphene modified diaphragm according to claim 3 or 4, characterized in that: The nano-vanadium-based compound is a product of further processing of nano-vanadium dioxide embedded with metal ions. The nano-vanadium dioxide embedded with metal ions is placed in a tubular furnace and heated. Under the conditions of adding a nitrogen source, a sulfur source and a carbon source, the heating temperature is 500-800° C. and the heating time is 0.1-4 hours to obtain nano-vanadium nitride embedded with metal ions, nano-vanadium sulfide embedded with metal ions, nano-vanadium carbide embedded with metal ions, nano-vanadium oxide embedded with metal ions having a nitrided surface, or nano-vanadium oxide embedded with metal ions having a sulfided surface.
6. The method for preparing the metal ion embedded nano-vanadium-based compound-graphene modified diaphragm according to claim 5, characterized in that: The nitrogen source includes ammonia, urea, and melamine; the sulfur source includes hydrogen sulfide, thiourea, and sulfur; and the carbon source includes carbon powder, glucose, and sucrose.
7. The method for preparing the metal ion embedded nano-vanadium-based compound-graphene modified diaphragm according to claim 8, characterized in that: The metal salt is one, two, three or more of sodium chloride, lithium chloride, zinc chloride, potassium chloride, calcium chloride, magnesium chloride, cobalt chloride, nickel chloride, ferric chloride and copper chloride.
8. The method for preparing the metal ion embedded nano-vanadium-based compound-graphene modified diaphragm according to claim 4, characterized in that: The organic liquid is one, two or more of ethanol, ethylene glycol, polyethylene glycol 200, polyethylene glycol 400 and polyethylene glycol 600.
Citation Information
Patent Citations
Synthesis method for in-situ compounding ZnV2O6 / graphene by [RMIM]X ionic liquid assisted microwave radiation method
CN111933931A
Self-assembled multilevel structure zinc vanadate modified lithium-sulfur battery diaphragm, preparation method thereof and lithium-sulfur battery with diaphragm
CN115693026A
Novel separators for electrochemical systems
US20130224632A1
Functional separator, manufacturing method therefor, and lithium secondary battery comprising same
WO2020085859A1